Kajian Subtitusi Tepung Porang (Amorphophallus Muelleri) Pada Tepung Terigu Terhadap Karakteristik Fisikokimia Dan Organoleptik Soft Cookies - Wulandari, Tanasya Mey; Damat, Damat; Wahyudi, Vritta Amroini (Food Technology and Halal Science Journal, 2023)
This research examines the "Study of Porang (Amorphophallus Muelleri) Flour Substitution in Wheat Flour on the Physicochemical and Organoleptic Characteristics of Soft Cookies". The first step in this research is the process of making soft cookies from the substitution of porang flour with wheat flour. Second, physicochemical and organoleptic analysis of soft cookies was conducted. This research was conducted using a simple Randomized Group Design (RAK) method. There were 6 treatments, namely P0 = 100% wheat flour: 0% porang flour, P2 = 90% wheat flour: 10% porang flour, P3 = 80% wheat flour: 20% porang flour, P4 = 70% wheat flour: 30% porang flour, P5 = 60% wheat flour: 40% porang flour, P6 = 50% wheat flour: 50% porang flour. There are 2 parameters tested, namely, porang flour and soft cookie products. The results showed that the ratio of porang flour addition significantly affected the physicochemical and organoleptic characteristics of soft cookies. The best soft cookies were obtained from treatment P2 (80% wheat flour: 20% porang flour). The test parameter values of P2 treatment are as follows: moisture content of 9.64%, fat content of 22.18%, fiber content of 1.09%, calcium oxalate content of 2.27%, texture of 44.14 N, brightness (L) of 44.32 and organoleptic scores on color parameters obtained value 4 (quite dark), aroma obtained value 3 (quite fragrant), taste obtained value 3 (good), texture obtained value 3 (soft), and liking obtained value 3 (like).